2022
DOI: 10.1007/s12035-022-02764-z
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant Variant of E2F4 Triggers Multifactorial Therapeutic Effects in 5xFAD Mice

Abstract: Alzheimer’s disease (AD) has a complex etiology, which requires a multifactorial approach for an efficient treatment. We have focused on E2 factor 4 (E2F4), a transcription factor that regulates cell quiescence and tissue homeostasis, controls gene networks affected in AD, and is upregulated in the brains of Alzheimer’s patients and of APPswe/PS1dE9 and 5xFAD transgenic mice. E2F4 contains an evolutionarily conserved Thr-motif that, when phosphorylated, modulates its activity, thus constituting a potential tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(49 citation statements)
references
References 98 publications
(156 reference statements)
8
39
1
Order By: Relevance
“…Recent studies in our laboratory have confirmed that the expression in neurons of both mouse and human E2F4DN prevents neuronal tetraploidy in 5xFAD mice [12]. Moreover, as expected from a multifactorial factor, neuronal expression of E2F4DN was able to mitigate other processes that become affected in AD such as neuroinflammation, A peptide proteostasis, and body weight loss [12], a known somatic alteration associated with AD [152].…”
Section: The Connection Of E2f4 With Admentioning
confidence: 69%
See 4 more Smart Citations
“…Recent studies in our laboratory have confirmed that the expression in neurons of both mouse and human E2F4DN prevents neuronal tetraploidy in 5xFAD mice [12]. Moreover, as expected from a multifactorial factor, neuronal expression of E2F4DN was able to mitigate other processes that become affected in AD such as neuroinflammation, A peptide proteostasis, and body weight loss [12], a known somatic alteration associated with AD [152].…”
Section: The Connection Of E2f4 With Admentioning
confidence: 69%
“…As observed in this cell line, as well as in mouse embryonic stem cells, E2F4 may activate or repress gene expression, according to its interaction partner [27,19]. Interestingly, E2F4 malfunction has been linked to cognitive impairment [94] as well as the ethiopathology of neurodegenerative diseases such as Alzheimer's disease (AD) [11,12]. This is consistent with a recent study that proposes E2F4 as a major regulator of most AD-specific gene networks [95], and with other bioinformatics-based studies suggesting that E2F4 participates in this disease [147][148][149].…”
Section: The Connection Of E2f4 With Admentioning
confidence: 80%
See 3 more Smart Citations